Musical monuments for the country house music, collection, and display at Tatton Park - Brooks, Jeanice (Oxford University Press, Oxford, 2010)
RESUMEN: This study uses the Library and Music Room at Tatton Park, Cheshire, to investigate how music collection by women fits into broader patterns of book acquistion and display c.1800, and how their activities influenced aspects of country-house design. It shows how women's music-making and its representation in the country house contributed both to new images of elite domesticity and to developing notions of an English musical heritage.